'My Name is Joe and I'm an Alcoholic': Addiction, Self‐knowledge and the Dangers of Rationalism. (June 2016) - Levy, Neil
Abstract: Rationalist accounts of self‐knowledge are motivated in important part by the claim that only by looking to our reasons to discover our beliefs and desires are we active in relation to them and only thereby do we take responsibility for them. These kinds of account seem to predict that self‐knowledge generated using third‐personal methods or analogues of these methods will tend to undermine the capacity to exercise self‐control. In this light, the insistence by treatment programs that addicts acknowledge that they are addicts seems puzzling. I argue that because addicts—and perhaps ordinary akratics, to some extent at least, too—are vulnerable to losing control of their actions via losing control over their beliefs, advising them to look to their reasons for actions is counterproductive and facilitates loss of control. In contrast, an insistence on what I call impersonal self‐knowledge, knowledge of some of one's states and dispositions generated by third‐personal means, may help to reestablish control.